Improvement of efficiency and viability in plasma gene transfection by plasma minimization and optimization electrode configuration. (27th June 2016) - Jinno, Masafumi; Tachibana, Kunihide; Motomura, Hideki; Saeki, Noboru; Satoh, Susumu
Abstract: Plasma gene transfection is expected as a safe and useful method of gene transfection. However, in this method, there is difficulty in keeping both high transfection efficiency and less cell damage simultaneously. The authors have evaluated transfection efficiency and cell viability using four different plasma sources, such as arc discharge, plasma jet, dielectric barrier discharge (DBD), and microplasma. A high transfection efficiency was achieved by discharge forms in which the electric current flows via the cells. This suggested that an electric current plays an important role in plasma gene transfection. The total volume of gas flow must be small or zero and the area in which the cells are directly irradiated by plasma must be small in order to achieve a higher cell viability. The microplasma that satisfies these conditions achieved both the highest transfection efficiency and the highest cell viability simultaneously.